160 Empowering future healthcare leaders and clinical researchers across a decade: UCLA’s Clinical and Translational Science Institute – Research Associates Program - Tiffany Chen; Laurie Shaker-Irwin; Noah Federman; Jim Morrison; Denise Gellene; Angshuman Saha; Brisa Garcia (Journal of Clinical and Translational Science, 2025)
Objectives/Goals: To assess the impact of UCLA’s Clinical and Translational Science Institute Research Associates Program (CTSI-RAP), a student-led undergraduate clinical research initiative, on current members’ career interests and development. Methods/Study Population: To evaluate CTSI-RAP’s impact, we surveyed students using the REDCap platform between May and June 2023. The survey captured data on demographics, academic background, motivations for joining, and engagement in clinical research activities. Students also provided self-assessments of how the program influenced their career interests. Both descriptive and qualitative analyses were then used to assess key factors influencing students’ experiences, including the program’s impact on career decisions in healthcare and clinical research. Results/Anticipated Results: Out of 43 students surveyed, 40 responded (93%). Before entering, 84.2% of students had less than one year of research experience, and most students (73.6%) did not have family members in healthcare or research professions. Top reasons for joining were gaining clinical research exposure, healthcare setting experience, and pursuing healthcare careers. Overall, 97% of students stated CTSI-RAP “definitely” or “most probably” confirmed their interest in medicine and 76% of students reported CTSI-RAP has “definitely” or “most probably” solidified their interest in clinical research. 100% of students who have applied for a job, professional school, scholarship, or internship included CTSI-RAP as a meaningful experience, reflecting the program’s mission to provide motivations for a career in medicine and science. Discussion/Significance of Impact: Since its establishment in 2013, CTSI-RAP has expanded from 15 students to more than 50 annually, providing hands-on clinical research and professional development opportunities. The program’s peer-mentorship and student-led approach have proven effective in preparing students for diverse healthcare and research pathways.